(untitled) (Research, Society and Development, 2021)
Brazil is the world’s largest consumer of pesticides. To monitor the quality of food sold in the country, the Program for Analysis of Pesticide Residues in Food (Programa de Análise de Resíduos de Agrotóxicos em Alimentos - PARA) was created, responsible for carrying out analyzes of these foods and providing annual reports. The objective of this study was to carry out a survey of the information contained in these reports on the residues of pesticides found on unsatisfactory samples (unauthorized pesticides and/or above the permitted limit). This is a descriptive documentary study, based on the reports available (2001 to 2018). Information was collected on the pesticides that most appeared among the samples considered unsatisfactory and their possible damage to human health. Strawberries, bell peppers, and cucumbers presented the largest numbers of samples unsatisfactory, mostly because of the presence of pesticides unauthorized. The pesticides that have been repeated the most irregularly were chlorpyrifos, carbendazim, acefate and metamidophos, the latter has been banned since 2011 in Brazil. Evidence show that such pesticides are toxic to the human organism. Measures are needed to better control and inspect food and pesticides sold in Brazil, also raise awareness among the population and rural producers.